The Organist as a Creator of Interaction in the Liturgy - Pulli-Huomo, Anna (Hymnologian ja liturgiikan seura, 2024)
‘In Thy Music, we will SEE the Music, In Thy Light, we will HEAR the Light…’1 In 1977, French composer and organist Olivier Messiaen (1908–1992), a Roman Catholic, lectured on the existence of music in the Cathedral of Notre Dame in Paris. He believed there were three types of sacred music: liturgical, religious, and one that breaks through to the beyond and is expressed through sound-colour [sic], resulting in a sensation of bedazzlement. According to Messiaen, liturgical music ‘celebrates God in His Church’ while ‘religious music discovers at every hour and everywhere’. Above these two is coloured [sic] music which ‘does that which the stained-glass windows and rose-windows of the Middle Ages did: they give us bedazzlement’ (Messiaen 1978: 2, 14, 15). As a Finnish Lutheran organist, I find these words of Messiaen speak to me about the mystery, role, and function of sacred music; in particular, how the coloured music he mentions interacts with earthly and afterlife realms and the profound experience it can evoke, for example, by bedazzlement.
Keywords: liturgia; liturginen musiikki; kirkkomusiikki; urut; urkurit